A Semiactive Skyhook-Inertance Control Strategy Based on Continuously Adjustable Inerter - Xiao-Liang Zhang; Tian Zhang; Jiamei Nie; Long Chen (Shock and Vibration)
This paper presents a modified skyhook-inertance control strategy which is realized through a hydraulic device of continuously adjustable inertance between sprung mass and unsprung mass. The parasitic damping inherent in the hydraulic device as well as the inertance is taken into account in the modified control strategy. Differential equation models are built to compare the performance of the semiactive suspension employing the modified control strategy with that of the passive suspension. The results demonstrate that the semiactive suspension significantly reduces sprung mass natural frequency, attenuates the resonant peak value without the penalty of deterioration at higher frequencies, and achieves over 28% improvement on ride comfort, compared with the passive suspension in unload condition. The proposed hydraulic device, together with its control strategy, can be used to reduce the variation of sprung mass natural frequency and ride comfort between unload and full-load condition.